Conditional survival analysis for patients with intraductal papillary mucinous neoplasms (IPMNs) undergoing curative resection. Issue 5 (May 2018) - Gaitanidis, Apostolos; Alevizakos, Michail; Tsaroucha, Alexandra; Tsalikidis, Christos; Simopoulos, Constantinos; Pitiakoudis, Michail
Abstract: Background: Conditional survival (CS) analysis represents a novel method that may provide more clinically relevant perspectives to cancer management compared to conventional survival analysis. The purpose of this study was to evaluate conditional survival for patients with intraductal papillary mucinous neoplasms (IPMNs) undergoing curative resection. Methods: A retrospective search of the Surveillance Epidemiology and End Results (SEER) database was performed. Three-year conditional survival (i.e. probability that a patient will survive an additional 3 years if they have already survived x years) was calculated using the formula 3- CS ( x )= OS ( x + 3 )/ OS ( x ), where OS represents overall survival. Results: Overall, 1303 patients were identified, with mean age of 65.2 ± 12.2 years. 3-CS at 1, 3 and 5 years after diagnosis was 35.8%, 47.5% and 44.7%. Patients with stage III/IV disease demonstrated small differences in 3-CS at 1–3 years after diagnosis compared to patients with stage I/II disease (I/II: 35.1%–46.9%, III/IV: 22.1%–42.3%, d range 0.09–0.28), while their 3-CS was superior at 4–5 years after diagnosis (I/II: 41.5%–45.7%, III/IV: 57.9%–64.7%, d range 0.24–0.47). Differences in 3-CS based on tumor grade displayed a different pattern, with small differences at 1–3 years after diagnosis (well-differentiated (WD)/moderately-differentiated (MD): 34.6%–50%, poorly-differentiated (PD)/undifferentiated (UD): 23.2%–40%, d range 0.18–0.24), before becoming prominent at 4–5 years after diagnosis (WD/MD: 50%–51.7%, PD/UD: 24.1%–30%, d range 0.4–0.55). Conclusions: Conditional survival for patients with IPMNs undergoing resection improves over time, especially for patients with high-risk features. This information may be used to provide individualized approaches to surveillance and treatment.